New probabilistic risk assessment of ethylhexyl methoxycinnamate: Comparing the genotoxic effects of trans- and cis-EHMC - Nečasová, Anežka; Bányiová, Katarína; Literák, Jaromír; Čupr, Pavel (Environmental toxicology, 2017)
Ethylhexyl methoxycinnamate (EHMC) is a widely used UV filter present in a large number of personal care products (PCPs). Under normal conditions, EHMC occurs in a mixture of two isomers: trans-EHMC and cis-EHMC in a ratio of 99:1. When exposed to sunlight, the trans isomer is transformed to the less stable cis isomer and the efficiency of the UV filter is reduced. To date, the toxicological effects of the cis-EHMC isomer remain largely unknown. We developed a completely new method for preparing cis-EHMC. An EHMC technical mixture was irradiated using a UV lamp and 98% pure cis-EHMC was isolated from the irradiated solution using column chromatography. The genotoxic effects of the isolated cis-EHMC isomer and the nonirradiated trans-EHMC were subsequently measured using two bioassays (SOS chromotest and UmuC test). In the case of trans-EHMC, significant genotoxicity was observed using both bioassays at the highest concentrations (0.5 - 4 mg mL-1 ). In the case of cis-EHMC, significant genotoxicity was only detected using the UmuC test at concentrations of 0.25 - 1 mg mL-1 . Based on these results, the NOEC was calculated for both cis- and trans-EHMC, 0.038 and 0.064 mg mL-1 , respectively. Risk assessment of dermal, oral and inhalation exposure to PCPs containing EHMC was carried out for a female population using probabilistic simulation and by using Quantitative in vitro to in vivo extrapolation (QIVIVE). The risk of cis-EHMC was found to be ∼1.7 times greater than trans-EHMC. In the case of cis-EHMC, a hazard index of 1 was exceeded in the 92nd percentile. Based on the observed differences between the isomers, EHMC application in PCPs requires detailed reassessment. Further exploration of the toxicological effects and properties of cis-EHMC is needed in order to correctly predict risks posed to humans and the environment. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 569-580, 2017.
Keywords: ethylhexyl methoxycinnamate; Mutagenicity Tests; Chromatography, Gas; hodnocení rizik; Female; přípravky chránící proti slunci; Sunscreening Agents; ženské pohlaví; genotoxicity; lidé; QIVIVE; trans/cis isomerisation; Risk Assessment; cinnamáty; Cinnamates; testy genotoxicity; probabilistic risk assessment; isomerie; Salmonella typhimurium; Isomerism; chromatografie plynová; Cosmetics; kosmetické přípravky; Humans